Pulsed electric fields to obtain healthier and sustainable food for tomorrow - Barba, Francisco (Francisco J.); Parniakov, Oleksii; Wiktor, Artur (Academic Press, 2020)
Pulsed Electric Fields to Obtain Healthier and Sustainable Food for Tomorrow illustrates innovative applications derived from the use of pulsed electric fields beyond microbial inactivation. The book begins with an introduction on how pulsed electric fields work and then addresses the impact of pulsed electric fields on bioaccessability/bioavailability and the development of nutraceuticals and food additives. Other sections explore the reduction of contaminants and assess the improvement of industrial process efficiency. A final section explores patents and commercial applications. This book will be a welcomed resource for anyone interested in the technological, physiochemical and nutritional perspectives of product development and the reduction of food toxins and contaminants. The concepts explored in this book could have a profound impact on addressing the concept of "food on demand," a concept that is a top priority in industry. --